Digital andragogy: A richer blend of initial teacher education in the 21st century - Blackley, S.; Sheffield, Rachel (2015)
This paper revisits the term ‘andragogy’ (adult education) and develops a new concept based upon an analysis of the skills and dispositions of 21st century learners in initial teacher education through the lens of adult education: ‘digital andragogy ’. In order to engage and retain students and revitalise education courses by optimising digital affordances, lecturers must examine the profiles of their learners and seek to create learning spaces that best suit their needs and wants. We posit that learners in initial teacher education programs should be encouraged and supported to transition from pedagogical practices experienced in their school years to higher education contexts for learning that are based upon digital andragogy.